A Workflow for Global Sensitivity Analysis of PBPK Models - McNally, Kevin; Cotton, Richard; Loizou, George D. (Frontiers in Pharmacology, 2011)
Physiologically based pharmacokinetic models have a potentially significant role in the development of a reliable predictive toxicity testing strategy. The structure of PBPK models are ideal frameworks into which disparate in vitro and in vivo data can be integrated and utilised to translate information generated, using alternative to animal measures of toxicity and human biological monitoring data, into plausible corresponding exposures. However, these models invariably include the description of well known non-linear biological processes such as, enzyme saturation and interactions between parameters such as, organ mass and body mass. Therefore, an appropriate sensitivity analysis technique is required which can quantify the influences associated with individual parameters, interactions between parameters and any non-linear processes. In this report we have defined a workflow for sensitivity analysis of PBPK models that is computationally feasible, accounts for interactions between parameters, and can be displayed in the form of a bar chart and cumulative sum line (Lowry plot), which we believe is intuitive and appropriate for toxicologists, risk assessors and regulators.